Urban rent restriction laws : Urban rent restriction ord. (1959) (as amended by Ordinance IX of 1979), Sind rented premises ord. (1979), Cantonments rent restriction act (1963) and amendments upto date latest caselaw - Janjua, Zia-ul-Islam; Lillah, Ehsan Ullah (Lahore Law Times Publications, 1980)
Includes a commentary.